Bridging the Gap: Orchestrating Indonesian Higher Education - Yudhoyono, Agus Harimurti; Nadia, Fiona Niska Dinda; Mudzakkir, Mohammad Fakhruddin; Suhariadi, Fendy (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study aims to ascertain the extent of the gap between the human resources presently available in the Republic of Indonesia (the number of study programs classified into fields of science existing in Indonesian higher education) and those required in the future to realize the Visi Indonesia Emas 2045. Furthermore, it seeks to identify how resource orchestration can narrow this gap through the lens of Resource Orchestration Theory (ROT). Design/Methods/Approach: The study employs a qualitative research methodology utilizing secondary data sources, namely higher education statistical data issued by the Ministry of Education, Culture, Research and Technology, and gross domestic product industrial data issued by the Indonesian Central Statistics Agency. Findings: This study finds a mismatch between the sector and study program by field of study both nationally and regionally. Nationally, some top sectors are not supported by specific study programs in accordance with their needs. Regionally, there is a mismatch between the distribution of study programs by field of study and the top industries in some region Originality/Value: This research contributes to the existing body of literature on ROT by exploring its applicability to the country’s human resources. While previous studies have employed ROT in organisational settings, this is one of the first to examine the theory in the country-level analysis. Furthermore, research on ROT has typically relied on surveys that are vulnerable to bias. This study, however, employs a distinctive and more comprehensive approach, namely the secondary data analysis. Practical/Policy implication: It is imperative that higher education institutions adopt a resource orchestration theory, which entails discontinuing study programs that fail to reflect the current and future priorities of the industrial sector. This necessitates the establishment of future-oriented programs of study that are aligned with the evolving requirements of the industry and the development of curricula that equip human capital with the skills and knowledge that are required in the future.